Directly Unproductive, Profit-Seeking (DUP) Activities - Bhagwati, Jagdish N. (Journal of Political Economy, 1982)
This paper proposes directly unproductive, profit-seeking (DUP) activities as a general concept that embraces a wide range of recently analyzed economic activities, including the subset of rent-seeking activities considered by Krueger. It then proceeds to provide a synthesis and generalization of the welfare-theoretic analysis of such activities by developing a fourfold categorization of cases depending on the levels of distortions before and after the DUP activity. Thus a unification and overview of the subject are achieved. In this paper, I begin in Section I by briefly discussing the common, unifying essence of the phenomena so analyzed and then arguing why they are best described as directly unproductive, profit-seeking (DUP) activities. Next, I proceed in Section II to differentiate analytically among different types of such activities, with a view of classifying them into categories which are analytically meaningful from the view-point of their welfare impact. Existing analyses of specific problems, such as tariff seeking and revenue seeking, are then readily identified in Section III as belonging to one such category or another, and the welfare consequences demonstrated in these analyses are then shown to be only specific illustrations of a wider class of DUP activities with identical welfare consequences.